The Stability of Money Demand in South Africa, 1965-1997 - Kevin S. Nell (University of Kent, Department of Economics, 1999)
After the adoption of more market-oriented monetary policy measures in 1980, the South African Reserve Bank primarily relied on setting predetermined growth targets for M3 to achieve its primary objective of price stability. The main purpose of this paper is to test empirically whether there exists a stable long-run demand for money function over the period 1965-1997. The empirical results suggest that there exists a stable long-run demand for money function for M3 in South Africa, while the demand for M1 and M2 display parameter instability following financial reforms since 1980. The results largely support the South African Reserve Bank's view that the M3 money stock could serve as an indicator for monetary policy.
Keywords: C22; E41; 330; Demand for Money; Stability; Cointegration; Geldnachfrage; Südafrika